Augmentation cystoplasty in neuropathic bladder. (3rd March 2020) - Reid, Sheilagh; Tophill, Paul; Osman, Nadir; Hillary, Chris
Abstract : Objectives: To look at the changing role of cystoplasty in the neuropathic population. Design: Retrospective case series. Setting: Single center over a 10-year period from 2004 to 2014. Participants and intervention: In 1995, the Princess Royal spinal injuries unit published the outcomes of 78 neuropathic patients who had undergone cystoplasty in the 10-year period from 1982 to 1992. [Singh G, Thomas DG. Enterocystoplasty in the neuropathic bladder. Neurourol Urodyn 1995; 14(1): 5–10.]. In this series, we review 51 consecutive patients undergoing the same operation over a 10-year period from 2004 to 2014 in the same single unit. Outcome measures: Demographic data were collected to include patient age, condition, and previous treatments. Pre- and post-operative details included sphincter insertions, renal function, continence rates, and complications. Results: Despite an increase in the number of patients seen at the unit, there were considerably fewer cystoplasty procedures performed in the current series (51 vs. 78 in the 1982–1992 series). There were also significantly fewer patients with spina bifida and fewer concomitant sphincter insertions in the latter series (eight patients vs. 52 in the 82/92 series). Nevertheless, similar outcomes are observed between the current and 1982–1992 series, with continence rates of 93.7 and 93.6%, respectively and low numbers of reported adverse events for both retrospective cohorts. Conclusions: Cystoplasty remains a safe and effective option for the management of neuropathic bladder in a carefully selected group of patients.